Coupled ER to Golgi Transport Reconstituted with Purified Cytosolic Proteins - Barlowe, Charles (The Rockefeller University Press, 1997)
A cell-free vesicle fusion assay that reproduces a subreaction in transport of pro-α-factor from the ER to the Golgi complex has been used to fractionate yeast cytosol. Purified Sec18p, Uso1p, and LMA1 in the presence of ATP and GTP satisfies the requirement for cytosol in fusion of ER-derived vesicles with Golgi membranes. Although these purified factors are sufficient for vesicle docking and fusion, overall ER to Golgi transport in yeast semi-intact cells depends on COPII proteins (components of a membrane coat that drive vesicle budding from the ER). Thus, membrane fusion is coupled to vesicle formation in ER to Golgi transport even in the presence of saturating levels of purified fusion factors. Manipulation of the semi-intact cell assay is used to distinguish freely diffusible ER- derived vesicles containing pro-α-factor from docked vesicles and from fused vesicles. Uso1p mediates vesicle docking and produces a dilution resistant intermediate. Sec18p and LMA1 are not required for the docking phase, but are required for efficient fusion of ER- derived vesicles with the Golgi complex. Surprisingly, elevated levels of Sec23p complex (a subunit of the COPII coat) prevent vesicle fusion in a reversible manner, but do not interfere with vesicle docking. Ordering experiments using the dilution resistant intermediate and reversible Sec23p complex inhibition indicate Sec18p action is required before LMA1 function.